Functional respiratory imaging after neostigmine- or sugammadex-enhanced recovery from neuromuscular blockade in the anesthetised rat: a randomised controlled pilot study - Schepens,Tom (2017)
Abstract Objectives Reductions in diaphragm activity are associated with the postoperative development of atelectasis. Neostigmine reversal is also associated with increased atelectasis. We assessed the effects of neostigmine, sugammadex, and spontaneous reversal on regional lung ventilation and airway flow. Methods Six Sprague-Dawley rats were paralysed with rocuronium and mechanically ventilated until recovery of the train-of-four ratio to 0.5. We administered neostigmine (0.06 mg.kg-1), sugammadex (15 mg.kg-1), or saline (n = 2 per group). Computed tomography scans were obtained during the breathing cycle. Three-dimensional models of lung lobes were generated using functional respiratory imaging technology, and lobar volumes were calculated during the breathing cycle. The diaphragmatic surface was segmented for the end-expiratory and end-inspiratory scans. The total change in volume was reported by the lung volume change from the end-expiratory scan to the end-inspiratory scan. Chest wall movement was defined as the lung volume change minus the volume change that resulted from diaphragm excursion. Results The two rats that received neostigmine exhibited a smaller relative contribution of diaphragm movement to the total change in lung volume compared with the two rats that received sugammadex or saline (chest wall contribution (%): 26.69 and 25.55 for neostigmine; -2.77 and 15.98 for sugammadex; 18.82 and 10.30 for saline). Conclusion This pilot study in rats demonstrated an increased relative contribution of chest wall expansion after neostigmine compared with sugammadex or saline. This smaller relative contribution of diaphragm movement may be explained by a neostigmine-induced decrease in phrenic nerve activity or by remaining occupied acetylcholine receptors after neostigmine.